2007
DOI: 10.1089/jam.2007.0638
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Spray Properties on Intranasal Deposition

Abstract: While numerous devices, formulations, and spray characteristics have been shown to influence nasal deposition efficiency, few studies have attempted to identify which of these interacting factors plays the greatest role in nasal spray deposition. The deposition patterns of solutions with a wide range of surface tensions and viscosities were measured using an MRI-derived nasal cavity replica. The resulting spray plumes had angles between 29 degrees and 80 degrees and contained droplet sizes (D(v50)) from 37-157… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
84
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(96 citation statements)
references
References 15 publications
6
84
0
2
Order By: Relevance
“…Materials penetrating the nasal valve available for deposition in the turbinate region are desirable. Both gamma scintigraphic measurements in human volunteers and nasal airway replicas have been used to study the deposition pattern of nasal delivery (62)(63)(64)(65)(66)(67). These studies identify several key parameters including plume angle, droplet size, plume velocity, and inspiratory flow rate that may influence the deposition pattern of nasal spray devices.…”
Section: Nasal Spraymentioning
confidence: 99%
“…Materials penetrating the nasal valve available for deposition in the turbinate region are desirable. Both gamma scintigraphic measurements in human volunteers and nasal airway replicas have been used to study the deposition pattern of nasal delivery (62)(63)(64)(65)(66)(67). These studies identify several key parameters including plume angle, droplet size, plume velocity, and inspiratory flow rate that may influence the deposition pattern of nasal spray devices.…”
Section: Nasal Spraymentioning
confidence: 99%
“…The olfactory region is located in the upper back quartile of the nasal cavity in a narrow slit approximately 1-2 mm wide. Traditional nasal pump devices used in most nasal drug delivery studies in humans are estimated to only deposit ≤5% of a typical dose in the olfactory region (15). Typical nasal pumps tend to have a wide plume angle that mainly deposit on the respiratory epithelium which would lead primarily to uptake in the blood stream and limit the percentage of drug directly distributed to the brain.…”
Section: Introductionmentioning
confidence: 99%
“…Cheng et al (2001) found that larger droplets and a wider spray angle increased deposition in the anterior region. Similarly, Foo et al (2007) found that sprays with small plume angles deposited more posteriorly but with minimal dependence on droplet size or viscosity. However, not all literature reports are consistent with this theory.…”
Section: In Vitro Deposition Characterization Of Nasal Spraysmentioning
confidence: 79%
“…The nose model was secured upright on a stand and connected to an Respirator Pump Model 613 (Harvard Apparatus, Holliston, MA, USA), which simulated a 15-breaths/min breathing pattern with a ratio of inspiration to expiration of 40/60 and a cycle volume of 700 mL/stroke. The administration angle has been shown to have a significant effect on the deposition pattern (Foo et al 2007;Kundoor and Dalby 2011;Shah et al 2013). The nasal spray was manually actuated at a 45 angle to the horizontal and at a nostril insertion depth of 5 mm into the cast upon inhalation.…”
Section: Assessment Of Deposition Patternmentioning
confidence: 99%